Chronostratigraphy of Upper Miocene-Quaternary volcanism in northern Costa Rica - Gillot, Pierre Yves (2011)
The Santa Rosa ignimbritic plateau (Bagaces Formation) of Upper Miocene to Late Pliocene age (between 8 to 1.6 m.y. ago), the north of Costa Rica, consists of a pile of pyroclastic flow deposits with minor interbedded lava flows and terrigenous sediments overlain by several pumice flow deposits (volume ca. 50 km3 DRE): Río Liberia pumice-flow deposit Formation (ca. 1.6 m.y. ago), Guayabo Pyroclastic Formation (between 1.5-0.6 m.y. ago), and Cañas pumice-flow deposit (<1 m.y.), and topped by the recent volcanic centers of the Guanacaste chain (< 600 000 years ago). This succession has been sampled for K-Ar dating. Aditional rocks were collected from the region between the Arenal volcano (active since 1968) and the Monteverde andesitic plateau in the north (2-1 m.y. ago). There are also more examples of relatively recent volcanism in this region, for example the San Miguel dome (<0.7 m.y. ago) in the fore arc, and Los Perdidos complex (caldera and domes) of Upper Quaternary age (ca. 0.1 Ma), which is overlaped by the dormant Chato volcano (38-3.5 x 103 years old) near the actual volcanic front. The total volume of volcanic rocks erupted during the Quaternary is equivalent to about 900 +/- 150 km3 of dense rock. The volume of basaltic andesitic magma is several times larger than the volume of silicic magma erupted during the same period. The age of silicic volcanism precedes and overlaps with the age ofthe Quaternary andesitic volcanic front, which is largely younger than 600 000 years. This study demonstrates that in the geodynamical evolutin of the Southern Central America Orogen Volcanism is one of alternating periods of huge volcanic activity separated by periods of relative reposal.